EFEKTIVITAS TEKNIK REMEDIAL UNTUK MENANGGULANGI KESULITAN BELAJAR IPA-BIOLOGI SISWA KELAS H SEMESTER I SLTP NEGERI 3 SRAGEN TAHUN PELAJARAN 2002 / 2003 - MARIDI MARIDI; MARYONO MARYONO; METTI SETYOWATI (Bioedukasi: Jurnal Pendidikan Biologi, 2005)
The objective of this research was knowing the effectiveness of the remedial technique toward some difficulties in studying biological science on second grade student of SLTP Negeri 3 Sragen in the academic year of 2002 / 2003 and comparing those two mwthods. This experimental research was carried out at SLTP N 3 Sragen. Purposive sampling technique was used on 66 students, Test technique was used, the data obtained then analyzed by t test.The results showed as follows: the average achievement before remedial treatment was of 4, 55 beside in a value of 6, 29 after treted (t observed 11, 30 > t table 2, 03).On the other hand, in the control , the average achievement before the conventional technique treatment was of 4,48, and after the treatment, the value was of 5.6 ( t obtained = 7,95 > t ud>ie - 2,03). The average increase of the students achievement for the experiment group was of 1, 74, beside the average increase of 1.16 for the control group, (t observed = 2, 74 > t = 1, 66). Those statistical data showed that there was significant difference of biological study achievement before and after the implementation of remedial and conventional technique. The data also showed that the remedial technique ismore effective than the conventional one.